2004
DOI: 10.1538/expanim.53.395
|View full text |Cite
|
Sign up to set email alerts
|

Refined Porcine Follicle Stimulating Hormone Promotes the Responsiveness of Rabbits to Multiple-Ovulation Treatment

Abstract: Abstract:We investigated whether refined follicle stimulating hormone (FSH) with only a little contaminating LH can promote the responsiveness of rabbits to multiple-ovulation treatment. One group of female rabbits was stimulated with refined porcine FSH (pFSH), an FSH source with low LH activity, and another group was treated with pFSH. The mean number of eggs recovered from donors stimulated with refined pFSH (27 ± 3) was significantly greater (P<0.05) than that with pFSH (20 ± 2). Furthermore, the mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Superovulation treatments with FSH diluted in PVP solutions have been tested and acceptable superovulation responses have been reported in distinct species, including rabbits (Kanayama et al. 1994; Hashimoto et al. 2004; Mehaisen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superovulation treatments with FSH diluted in PVP solutions have been tested and acceptable superovulation responses have been reported in distinct species, including rabbits (Kanayama et al. 1994; Hashimoto et al. 2004; Mehaisen et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, animal manipulation can be minimized if FSH is dissolved in polyvinylpyrrolidone (PVP), which permits longer intervals between treatments (one injection every 24 h) given its ability to prolong the clearance rate in vivo of many molecules by binding and stabilizing them. Superovulation treatments with FSH diluted in PVP solutions have been tested and acceptable super-ovulation responses have been reported in distinct species, including rabbits (Kanayama et al 1994;Hashimoto et al 2004;Mehaisen et al 2006). Nevertheless, results of superovulation treatments vary, and one of the reasons for this may be the variable LH : FSH ratio, when preparations isolated from the pituitary gland are used.…”
Section: Introductionmentioning
confidence: 99%
“…They were fed pelleted rabbit chow (Oriental Yeast Co., Shizuoka, Japan) and filtered water ad libitum. Multiple ovulation treatments were performed as described previously (Hashimoto et al 2004). In brief, super-ovulation of female rabbits was induced by a single subcutaneous injection of 3-AU refined porcine follicle stimulating hormone (FSH; Antrin R, Denka Pharmaceuticals Inc., Kanagawa, Japan) dissolved in 10% polyvinylpyrrolidone (168-03115, K-90, Wako Chemical Industries, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The extra glycosylation sites give hCG a longer half‐life (Le Cotonnec, Porchet, Beltrami, & Munafo, ; Mannaerts, Geurts, & Odink, ). In rabbits, the effect of LH on superovulation has been studied using purified porcine FSH, obtaining highly variable results (Hashimoto et al, ; Salvetti et al, ). Our studies with recombinant human gonadotropins (rhFSH either alone or in combination with rhLH) suggested that the window of LH in rabbits is FSH dose‐dependent (Viudes‐de‐Castro, Pomares, Saenz de Juano i Ribes, Marco‐Jiménez, Vicente, ).…”
Section: Introductionmentioning
confidence: 99%